Pengaruh Motivasi Belajar dan Teman Sebaya Terhadap Minat Belajar Peserta Didik Kelas XI SMAN 36 Jakarta - Harliani, Rossa; Sudiarditha, I Ketut; Zahra, Siti Fatimah (Jurnal Serambi Ekonomi dan Bisnis, 2024)
This study aims to analyze the direct effect of learning motivation and peers on the interest in learning of students in class XI of SMAN 36 Jakarta. This study also analyzes peers in mediating the indirect effect of learning motivation on students' interest in learning class XI of SMAN 36 Jakarta. This study uses quantitative methods by using primary data through distributing questionnaires to 180 students of class XI of SMAN 36 Jakarta. The analysis technique used in this research is Structural Equation Model (SEM) with Partial Least Square (PLS) or known as SEM-PLS. The results of this study indicate that there is a positive and significant effect of learning motivation on the interest in learning of students in class XI of SMAN 36 Jakarta directly. In addition, there is a positive and significant indirect effect of learning motivation on the interest in learning of students of class XI of SMAN 36 through peers as a mediating variable. These findings suggest that increasing students' motivation and building a supportive peer environment are essential to increase students' interest in learning.